Lung Cancer Risk and Genetic Polymorphisms in DNA Repair Pathways: A Meta-Analysis - Kiyohara, Chikako; Takayama, Koichi; Nakanishi, Yoichi (Journal of Nucleic Acids, 2010)
Genetic variations in DNA repair genes are thought to modulate DNA repair capacity and are suggested to be related to lung cancer risk. We conducted a meta-analysis of epidemiologic studies on the association between genetic polymorphisms in both base excision repair and nucleotide excision repair pathways, and lung cancer. We found xeroderma pigmentosum complementation group A (XPA) G23A (odds ratio (OR) =0.76, 95% confidence interval (CI) =0.61–0.94), 8-oxoguanine DNA glycosylase 1 (OGG1) Ser326Cys (OR=1.22, 95% CI=1.02–1.45), and excision repair cross-complementing group 2 (ERCC2) Lys751Gln (OR=1.27, 95% CI=1.10–1.46) polymorphisms were associated with lung cancer risk. Considering the data available, it can be conjectured that if there is any risk association between a single SNP and lung cancer, the risk fluctuation will probably be minimal. Advances in the identification of new polymorphisms and in high-throughput genotyping techniques will facilitate the analysis of multiple genes in multiple DNA repair pathways. Therefore, it is likely that the defining feature of future epidemiologic studies will be the simultaneous analysis of large samples of cases and controls.